Infecção genital por Clhamydia Trachomatis em gestantes : prevalência e fatores associados - Ibiapina, Flávio Lúcio Pontes (2008)
To estimate the prevalence of Chlamydia trachomatis in pregnant women, comparing the positive group to the negative one in respect to socio-demographic factors, gynecologic history and exam, evaluating the risk factors associated to Chlamydia trachomatis genital infection. Subjects and methods: Hybrid capture test for Chlamydia trachomatis was performed in 446 pregnant women at Hospital Geral Dr César Cals, from the Health Secretary of the State of Ceará, from August, 2003 to May, 2004. Medium age in the group was 25.98 years and 19 weeks was the medium age of pregnancy. A structured questionnaire was applied, no matter the age of pregnancy, whether they were or not symptomatic, excluding those who had used antibiotics or any other substance into the vagina, during the previous fifteen days or who had kept sexual relationship until two days before the consultation, with a endocervical swab being performed, in order to have a hybrid capture test for the presence of Chlamydia trachomatis, as indicated by the manufacturer. Data were analysed by STATA 13.0, performed by means of the qui-square and logistic regression tests with descriptive and analytic presentation. Results: The prevalence of Chlamydia trachomatis among the pregnant women was 2.91%. Risk factors independently associated to Chlamydia trachomatis genital infection were history of pelvic pain or pelvic inflammatory disease, vulvar discharge and not using condom with an eventual sex partner. Respective odds ratio and confidence intervals were calculated to these variable. Conclusions: The positive group was younger, had smaller salaries and presented a greater frequency of divorced women, with less preservative use and more positive history of genital discharge and pelvic pain in the past. The OR to the presence of Chlamydia trachomatis genital infection was 1, 7 for those women not using condom and 0, 10 and 0, 17, respectively for a negative history of pelvic pain / PID, and the absence of vulvar discharge.